Investigating policy tools and variables to support collaborative governance and collective learning: a programmatic assessment of the Collaborative Forest Landscape Restoration Program - McIntyre, Kathleen B., author; Schultz, Courtney, advisor; Cheng, Tony, committee member; Fernández-Giménez, Maria, committee member; Duffy, Robert, committee member (Colorado State University. Libraries, 2019)
Collaborative governance has increased in prominence as a potential policy tool to support natural resource management within forest contexts. Until recently, there has been little formal space within the governance regime to support collaboration. The Collaborative Forest Landscape Restoration Program (CFLRP) was authorized by Congress in 2009 to facilitate large landscape restoration projects on federal forest lands through a focus on fire-adapted ecosystems, a mandate to monitor, and a mandate to collaborate throughout the lifetime of the project. In 2017, we conducted a third-party programmatic review of the CFLRP program to assess both theoretical and applied implications of this policy within the collaborative forest restoration context. This dissertation seeks to examine policy that supports collaboration and collective learning within US forest management contexts, and answer questions regarding whether collaborative policy innovations garner collaborative benefits. I also examine the challenges groups face, the factors that influence collaboration, and what types of collective learning activities occur under collaborative policy innovations. Using qualitative research methods including participant observation and interviews, I address these practical and theoretical research questions through three chapters (Chapters 2, 3, and 4). In Chapter 2, I assess to what extent the CFLRP program supported collaborative governance and seek to identify the variables that influence and support collaboration. This chapter reports on the theoretical research questions regarding collaborative benefits interviewees attributed to the program and the various top-down, structural and local, contextual variables that influence collaboration on projects. From these findings, I draw conclusions regarding policy tools and policy implementation to support collaborative governance in forest management. Chapter 3 addresses to what extent the CFLRP program supported collective learning activities and outcomes and the variables that may influence successful collective learning across the program. Collective learning is closely related to collaborative governance and critical to ensuring collaboration and adaptive governance are successful in terms of sharing lessons learned. We identify a variety of activities occurring on each project and then across projects that indicate a level of collective learning within the CFLRP program and ultimately a system of multi-level network governance. These findings have larger implications for building public-private partnerships in an era of decreasing agency budgets and staff capacity. Lastly, Chapter 4 addresses our more applied research objectives regarding the benefits and challenges reported under the CFLRP program. This chapter specifically seeks to identify the value-added and challenges of the program as reported by participants. I report on the practice and policy implications from the CFLRP program in terms of collaborative forest restoration policies within US natural resource governance contexts. The CFLRP program provided a unique opportunity to programmatically assess whether policy can effectively support collaboration, the various local, contextual and top-down, structural variables that were influential in terms of collaborative success, and whether the program was supporting collective learning activities and outcomes. This dissertation sought to fill these research gaps and contribute to the collaborative governance and forest management literature. Within my conclusion, I review the major themes across my chapters and propose future research directions and questions regarding forest management and collaborative governance. Ultimately, my chapters show that there are variety of variables both top-down, structural and local, contextual that both support and facilitate collective learning and collaborative governance, which has implications for crafting more effective natural resource policies. Our research indicates that the CFLRP program effectively supported collaboration and collective learning, and generated a variety of valuable benefits that contributed to the accomplishment of more holistic restoration work and indicated that collaboration can be a valuable policy tool for natural resource management in the future.